Recombinant viral proteins delivered orally through inactivated bacterial cells induce protection in Macrobrachium rosenbergii (de Man) against White Tail Disease - NaveenKumar, Singaiah (Journal of fish diseases, 2021)
© 2020 John Wiley & Sons Ltd.